Efektivitas Guide Journaling Dalam Menurunkan Tingkat Overthinking Pada Mahasiswa Aktif Organisasi - Cholila Shinta Jatisari; Adelia Cantika Putri; Syifa Nafissa; Auliyah Hamzah Hakikie; Nia Damayanti; Mesya Akila; Muhammad Abi Nubli; Miftahul Hanif (CV. Era Digital Nusantara, 2025)
This study aims to examine the effectiveness of guided journaling in reducing overthinking levels among active organization students of the 2025 cohort at the Faculty of Psychology, UIN Raden Fatah Palembang. Overthinking is defined as the tendency of individuals to think about a problem, event, or possibility excessively, repeatedly, and in an uncontrollable manner, resulting in anxiety and hindering decision-making processes. The research method used is quantitative experimental with a Two Group Pretest-Posttest Design. The research subjects consisted of 20 students randomly assigned into an experimental group (n=10) receiving guided journaling intervention for 14 days, and a control group (n=10) receiving no treatment. Data were collected using the Penn State Worry Questionnaire (PSWQ) consisting of 16 items. Data analysis used the Independent Sample t-Test and Paired Sample t-Test with the IBM SPSS Statistics application. The results of the Independent Sample t-Test indicated a significant difference between the experimental and control groups after the intervention was given (t = 4.209; p = 0.001 < 0.05). The results of the Paired Sample t-Test showed a significant decrease in overthinking scores in the experimental group, from a pretest mean of 58.90 to 40.00 at posttest (t = 5.294; p = 0.000 < 0.05). This study is expected to provide information on the importance of guided journaling as a self-help intervention, as it is a practical and accessible strategy to help students manage excessive thinking and improve mental well-being.